PERAN WORLD WIDE FUND FOR NATURE (WWF) DALAM PERLINDUNGAN BADAK DI AFRIKA SELATAN TAHUN 2010-2014 - Rino Seffitra; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aims to analyze the role of World Wide Fund for Nature (WWF) in Rhino Protection in South Africa. South Africa has the highest rhino population in Africa. As home for the African rhinoceros, South Africa faced by the high level of rhino poaching because that, the rhino population in South Africa getting decreased every year since 2010.This research use library research method. All data in this research collected from books, literature, magazine articles, journals, bulletins, documents and websites. This research use international organization level of analyze that focused on WWF. Besides that, this research also using pluralism perspective the assumpt state is not the single actor in international relations.This research concluded that WWF’s role to influence the South African government to improve monitoring and make a policy for rhino conservation. WWF success to ask the South African government to establish cooperation with rhino’s horn consumer countries to combat rhino poaching in South Africa. Besides that, WWF and South African government made a cooperation to stopping rhino poaching in some national parks of South Africa.Keywords: role of WWF, rhino poaching, protect, South Africa